Miss USSR - Gordeeva, Valentina (Great Britain, 2017)
"Miss USSR 2017" is a feature-length documentary film that takes us through the inner workings of a Beauty Pageant Miss USSR UK 2017 and gives an unprecedented access to the backstage of the show. Following contestants the film explores the hopes and dreams of young women from former Soviet Union countries as they compete for the title of the next Miss USSR UK.
Verzio Film Festival Submission
Keywords: Documentary films